Roles of long noncoding RNA in lung cancer - Liu, Yan-ru; Zhang, Rui-feng; Ying, Ke-jing (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2014)
Long noncoding RNAs are a group of noncoding RNAs with a length more than 200 nucleotides. Recent studies have revealed that long noncoding RNAs play an important role in the development and progression of cancer. Lung cancer is the leading cause of cancer-related death all over the world. In this article, we review the roles of long noncoding RNAs in lung cancer to provide new insights into the diagnosis and treatment of the disease.